PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN KUALITAS GURU TERHADAP KINERJA GURU UNTUK MENINGKATKAN PRESTASI SEKOLAH DASAR SWASTA DI KECAMATAN JOMBANG KOTA CILEGON - Ahmad Refudin; Budi Ilham Maliki; Muhammad Suparmoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is the foundation of national development and progress. In Jombang District, Cilegon City, there is a gap in achievement between private and public elementary schools, with public schools being more dominant in various competitions. This study aims to analyze the influence of principal leadership and teacher quality on teacher performance and school achievement, both directly and indirectly through teacher performance as a mediating variable. This study uses a quantitative approach with a descriptive-verification correlation survey method. Data were collected through Google Form from 100 private elementary school teachers in Jombang District, and analyzed using the SEM PLS technique. The results of the analysis show that principal leadership has a significant effect on teacher performance (significance value 0.009), but not significant on school achievement (value 0.070). Teacher performance and teacher quality have a positive and significant effect on school achievement, with significance values of 0.000 and 0.006, respectively. In addition, teacher performance is proven to mediate the influence of principal leadership and teacher quality on school achievement, with significance values of 0.013 and 0.000, respectively. From the hypothesis test, it is concluded that all variables have a positive and significant effect except for the direct effect of principal leadership on school achievement, which is not significant.